Theoretical and Experimental Research on Gun Propellant Burning - Gabriel F. NOJA (Wojskowa Akademia Techniczna, 2022)
The paper presents a method to determine the burning rate law and the progressivity coefficient of the fine-grained propellants shape. To achieve the objective of this paper, a series of tests were performed in a closed vessel. The results obtained from these tests were processed to determine experimentally the burning rate and the progressivity coefficient of the propellant shape starting from the premise that the burning surface has identical values for the same value of the volume fraction of burned propellant in two closed vessel tests at different loading densities. The experimental determination of the progressivity coefficient of the propellant shape shows that irregularities of the shape of the fine-grained propellants and gradual ignition lead to values completely different from the theoretical ones.
Keywords: Balistyka wewnatrzna (pirostatyka)